Security Challenges and Foreign Direct Investment in Nigeria: Implications for Economic Growth (2010 – 2024) - Mathias O. Ananti; Okoye Joy Ndidiamaka; Ezeneme, Ebele Victoria (Milestone: Journal of Strategic Management, 2025)
This paper examines the effects of security threats on Foreign Direct Investment (FDI) in Nigeria and their broader implications for economic growth. This study adopts a content analysis method to systematically review policy documents, academic papers, news reports, and reports from international organizations published between 2010 and 2024. The analysis focuses on the impact of insurgency, ethnic and religious strife, militancy, kidnapping, and herdsmen-farmer violence on foreign investment inflows and economic stability. Findings reveal that persistent security risks significantly deter foreign capital inflows and disrupt economic activities. Insurgent groups, such as Boko Haram in the North-East, have triggered humanitarian crises and economic stagnation, while ethnic and religious conflicts heighten insecurity. Niger Delta militancy disrupts oil production, and the rise in kidnappings and criminal violence increases business costs and investment risks. Additionally, herdsmen-farmer conflicts weaken agricultural productivity and discourage rural investment. The study highlights the necessity of comprehensive security sector reforms, targeted financial support, and infrastructure development programs to restore investor confidence and sustain economic growth. It recommends enhanced national security investments, financial incentives for security infrastructure, and strategic recovery plans for affected sectors. Addressing these security challenges is essential to creating an environment conducive to sustainable economic development and attracting foreign investment.